PENERAPAN METODE PEMBELAJARAN OPEN ENDED PROBLEM PADA MATA PELAJARAN IPS / EKONOMI DENGAN KOMPETENSI DASAR KELANGKAAN SUMBER DAYA DAN KEBUTUHAN MANUSIA GUNA MENINGKATKANAKTIVITAS DAN HASIL BELAJAR SISWA KELAS VIII-B SMP NEGERI 2 SATU ATAP BOTOLINGGO - Irma Noervadila (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
one factor which affected low learning outcomes was the effectiveness of learning method which implemented in the teaching and learning process. By applying open ended problem learning method, students were ordered to discover their own knowledge through the togetherness learning process with their feiends on their group which guided by teachers. The purpose of this study was to describe the implementation of open ended problem learning method to increase student’s learning activitiy and learning outcomes. This study was classroom action research, which was held at State Junior High Boarding School 2 Botolinggo. This study was focused to the students of Grade VIII-B as many as 30 students. Learning outcomes data on pre-cycle showed that from 30 students, there were 9 students who can’t reach the minimum mastery criteria, and 21 other students were passed minimum mastery criteria with classical mastery percentage degree 70%. This low learning outcome was caused by student’s passive activity in learning process. On the other hand, based on observation result, student’s learning activity was on “active” category. The increase of student’s learning outcome on the second cycle reached 86,67%. There were 4 students who can’t reach the minimum mastery criteria and the other students have been reached the minimum mastery criteria. By achieving the classical mastery, this study will not continue to the next cycle, or this study will be stopped.